Green Wheels: Solaris Campus Cruiser in Action - Aswathy A.S.; Anandhu B; Ananthakrishnan K.P; Supriya S.P; Shibin D.H (International Journal of Energy and Thermal Applications, 2024)
The publicly funded transportation system has become expensive due to the growing trends of industry and global economic growth, which have resulted in fluctuating gas prices and other price increases. Innovation can be used to solve any of these issues. Improving the usage of renewable energy sources, such as solar power, in place of fossil fuels is one of the most practical ways to address the problems. The aspiration of all people to possess a solar car that may be used for commerce is gradually coming true. Affordable electric automobiles are now accessible. This chance is used to design a four-wheeler driven by solar energy. The vast and intricate facets of many different disciplines are covered in the multidisciplinary field of renewable energy the design of vehicles. The photovoltaic system in the car is its power source, and the produced voltage it stores in its battery feeds the Continuous The magnet DC motor, which turns the vehicle’s rear wheels.
Keywords: Electric vehicle; Lead Acid Battery; Permanent Magnet D C Motor; Solar Charge Controller; maximum power point tracking